2024
DOI: 10.1093/gbe/evae022
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of DNA Methylation as a Driver of Plastic Responses to the Environment Across Cells, Organisms, and Populations

Samuel N Bogan,
Soojin V Yi

Abstract: There is great interest in exploring epigenetic modifications as drivers of adaptive organismal responses to environmental change. Extending this hypothesis to populations, epigenetically driven plasticity could influence phenotypic changes across environments. The canonical model posits that epigenetic modifications alter gene regulation and, subsequently impact phenotypes. We first discuss origins of epigenetic variation in nature, which may arise from genetic variation, spontaneous epimutations, epigenetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 176 publications
(233 reference statements)
2
5
0
Order By: Relevance
“…We found clear evidence of DNA methylation reducing gene expression variability, or transcriptional noise, in a sex-specific manner in response to elevated pCO 2 . These findings align with the growing consensus that gene body methylation may not have a direct regulatory role in gene-level expression, but instead functions to broadly reduce transcriptional variation across the genome [32,50,51]. Additionally, differences in gene activity and methylation patterns between female and male oysters highlight the need to examine how OA may affect reproduction differently in females and males [21], and underscore the cell- and tissue-specificity of DNA methylation [52,53].…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…We found clear evidence of DNA methylation reducing gene expression variability, or transcriptional noise, in a sex-specific manner in response to elevated pCO 2 . These findings align with the growing consensus that gene body methylation may not have a direct regulatory role in gene-level expression, but instead functions to broadly reduce transcriptional variation across the genome [32,50,51]. Additionally, differences in gene activity and methylation patterns between female and male oysters highlight the need to examine how OA may affect reproduction differently in females and males [21], and underscore the cell- and tissue-specificity of DNA methylation [52,53].…”
Section: Discussionsupporting
confidence: 83%
“…Although there is limited evidence for DNA methylation driving differential gene expression, it is possible that methylation may change transcriptional opportunities. Sparse methylation may allow for exon skipping or access to alternative start sites, thereby modifying gene expression and phenotype [31,32,55]. We observed that elevated pCO 2 elicits alternative splicing, although environmentally-responsive splicing accounted for a small proportion for the total splicing variance.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations